Christian education in the family. (Journal of Parents and Teachers, 2014)
It is well known that educating children is not an easy task, but it is a fundamental and exciting mission in which, by evangelizing them, we evangelize ourselves again. The article explains how to convey beliefs and how to form a family within the framework of the Christian faith.
Keywords: Religion; educating in faith; transmitting values; evangelizing; Christianity.